Development of an Injector Bracket for Precise and Efficient Fuel Spray Inspection in the Combustion Chamber of the Mercy Axor 2528 Unit at PT Antareja Mahada Makmur Site MIFA, April – July 2025 - Alrazzak, Fajri; G , Nanang Sofiyulloh (Green Publisher Indonesia, 2025)
The fuel injector system on the Mercy Axor 2528 functions to spray fuel (diesel) into the engine combustion chamber with the right amount and time, so that the combustion process runs efficiently. The injectors ensure that the fuel is mixed with the right amount of air, resulting in a perfect and efficient combustion. The occurrence of low power in the injector is due to fuel dilution this condition where the fuel is mixed with engine oil which can reduce lubrication performance and potential engine damage. This condition occurs when fuel (usually diesel) leaks and mixes with engine oil, resulting in a decrease in viscosity and the ability of the oil to effectively lubricate engine components. Where if the injector is damaged, repair actions are carried out to replace the